Borrowing from "Pui" to Pay "Pom": Multiple Borrowing and Over-Indebtedness in Rural Thailand. (October 2017) - Chichaibelu, Bezawit Beyene; Waibel, Hermann
Highlights: The paper is one of the first to identify the bidirectional relationship between multiple borrowing and over-indebtedness in Thailand. Taking up multiple loans increases a household's probability of being over-indebted. Over-indebtedness does not lead households to take more loans to refinance old debts. Over-indebtedness and multiple borrowing are persistent problems for rural households in Thailand. Income shocks are the major cause of multiple borrowing for poor households. Summary: Rural financial markets have grown rapidly in Asian emerging market economies, thus contributing to economic development and the reduction of poverty. At the same time, however, the level of indebtedness of rural households has increased, making households more vulnerable to shocks. One of the reasons for rising household debt is the ease of borrowing simultaneously from a growing number of lending institutions. This paper addresses two major questions. First, does borrowing from multiple sources increase rural households' risk of over-indebtedness? Second, do over-indebted rural households refinance their outstanding loans through multiple borrowing, running the risk of becoming trapped in a debt cycle? Employing a dynamic random effects bivariate probit model for a unique set of longitudinal household panel data from Northeast Thailand, this study examines the bidirectional relationship between over-indebtedness and multiple borrowing to determine to what extent rural households become trapped in debt cycles. On the one hand, the results indicate that households in Northeast Thailand take on multiple loans, which further increases their risk of becoming over-indebted. On the other hand, our model results do not confirm the widespread notion that over-indebted rural households use multiple loans to refinance unpayable debts.